Tendencje globalizacyjne i integracja a zmiany modelu biznesu polskich przedsiębiorstw - Gołębiowski, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Globalization and economic integration result in growing competition. In order to build the international competitiveness of Polish firms it is necessary to change their business models. Selected suggestions for changes of business models of Polish companies are presented in the paper. Discussion is focused on desired changes of Polish firms' attitude toward creation of customer value, with suggested emphasis on differentiation-based value components rather than on its cost-to-customer-rclaied component. Market segmentation and international scope of business operations are also discussed in the context of possible penetration of larger international target markets (including euro-segments) by Polish firms. Finally, the decisions on vertical integration in the context of company internationalization are presented.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 113-123